Selective Anti-melanoma Effect of Phosphothioated Aptamer Encapsulated by Neutral Cytidinyl/Cationic Lipids - Wu, Jing; Wang, Shuhe; Li, Xiang; Zhang, Qi; Yang, Jie; Ma, Yuan; Guan, Zhu; Yang, Zhenjun (Frontiers in Cell and Developmental Biology, 2021)
BC15-31 is a DNA aptamer that targets heterogeneous nuclear ribonucleoprotein A1 (hnRNP A1), which plays a crucial role in the process of pre-RNA maturation and is also essential for the rapid proliferation of tumor cells. In this research, we modified BC15-31 with a phosphorothioate (PS) backbone, LNA and 2ʹ-O-MOE to enhance its stability and target affinity. In addition, a neutral cytidinyl lipid (DNCA) and a cationic lipid (CLD) were mixed to encapsulate modified aptamers with the aim of improving their cell permeability with low toxicity. Under the DNCA/CLD package, aptamers are mainly distributed in the nucleus. A modified sequence WW-24 showed an excellent selective anti-melanoma (A375 cells, ~25 nM, 80%) activity, targeted to both hnRNP A1 and hnRNP A2/B1 found by BLI experiment, induced more early and late apoptosis in vitro, which also showed stronger antitumor effect and longer accumulation time in vivo. These results provide a new strategy for further clinical applications.